Corporate Governance Challenges for Small and Medium Enterprises in the Constrained Zimbabwean Economy - Mufaro Dzingirai; Shingirai Sikomwe; Noah Tshuma (IGI Global, 2023)
Although corporate governance has become a topical issue around the world in recent years, it is surprising to note that SMEs were much neglected in this corporate governance wave. Therefore, this study aims to establish the corporate governance challenges confronting Small and Medium Enterprises(SMEs) in the economy of Zimbabwe. This study is prompted by the dwindling performance experienced by SMEs. Notably, the study adopts an interpretivism research philosophy and the exploratory research design given that the study was the first of its kind. The corporate governance challenges which emerged from the data analysis are succession disputes, ownership concentration, lack of disclosure issues, limited resources, and lack of systems and structures. Therefore, it is recommended that SMEs should put in place a clear succession matrix in order to enable good corporate governance. Moreover, this study recommends that SMEs should strive to ensure that there is a separation of ownership and control in order to align with the best international corporate governance principles and practices.